Machine translation and foreign language education - Urlaub, Per; Dessein, Eva (Frontiers in Artificial Intelligence, 2022)
Online machine translation tools have great potential to transform foreign language education. This essay will synthesize systematic research on the role of machine translation conducted in the field of educational linguistics. After describing approaches developed that promote the integration of machine translation into language learning environments, the essay will briefly outline lingering concerns associated with the integration of MT tools into educational settings. We will propose future R&D priorities that can generate products based on existing technologies that have the potential to support language learners more optimally compared to existing machine translation tools. We conclude that an acknowledgment of the difficulties of MT tools to handle socio-culturally complex source text would pave the way for the development of MT-based pedagogical tools.